1998
DOI: 10.2337/diacare.21.3.438
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying Delay and Gastric Electrical Derangement in IDDM

Abstract: Delay of gastric emptying time and gastric electrical abnormalities are found in a high proportion of children with diabetes and can contribute to poor glycemic control, most likely by causing a mismatch between the onset of insulin action and the delivery of nutrients into the small intestine. Diabetic children with unexplained poor glycemic control should be investigated for abnormalities in gastric motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 24 publications
(34 reference statements)
7
71
2
1
Order By: Relevance
“…Both bradygastria [25] and tachygastria [26] , conditions associated with delayed gastric emptying [27] , have been found after vasopressin stimulation in the human stomach. Altogether, these studies suggest that vasopressin and its receptors are involved in gastrointestinal motility, and the demonstration of vasopressin receptor mRNA in the gastrointestinal tract in this study may be related to this action.…”
Section: Discussionmentioning
confidence: 99%
“…Both bradygastria [25] and tachygastria [26] , conditions associated with delayed gastric emptying [27] , have been found after vasopressin stimulation in the human stomach. Altogether, these studies suggest that vasopressin and its receptors are involved in gastrointestinal motility, and the demonstration of vasopressin receptor mRNA in the gastrointestinal tract in this study may be related to this action.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the differences in gastric emptying rate and gastrin plasma concentrations in the three groups warrant discussion. Previous studies have shown that gastric emptying was delayed in symptomatic and asymptomatic diabetic patients with AN [4,11,[16][17][18]. Gastric emptying is abnormal in about 50% of diabetic patients, and delay in gastric emptying of nutrientcontaining meals is more common than rapid emptying [19].…”
Section: Discussionmentioning
confidence: 99%
“…Gastroparesis has been shown to be significantly correlated with a poor metabolic control in a population of T1D children with gastric electrical abnormalities. (Cucchiara et al, 1998). Furthermore it is conceivable that delayed gastric emptying may cause a mismatch between the onset of insulin action and the delivery of nutrients into the small intestine (Rayner et al, 2001).…”
Section: Gastropathymentioning
confidence: 99%